Saberes docentes em Matemática mobilizados no processo de formação de professores em um curso normal de nível médio - Cabral, Vilmara Luiza Almeida (2020)
The present dissertation, developed in the line Teacher Training of the Postgraduate Program in Science and Mathematics Teaching - Professional Master's at the State University of Paraíba (UEPB) aimed to discuss teaching knowledge in Mathematics in the process of initial training in a Normal course. of Technical Level. This choice is justified by the concern with the Mathematics training offered at the Normal School and its impacts on the Initial Years of Elementary School, since many graduates are inserted in the professional market of the city. The present work had a theoretical foundation based on Tardif (2010), Shulmam (2005) who discuss professional knowledge, and Curi (2004) who investigated Mathematics training in the Early Years, among other authors. Our methodological proposal had a guiding principle anchored in qualitative, exploratory and case study research. The study had as research subjects two teachers from the normal school, both teaching in the 3rd and 4th year in the Normal Teaching modality, in the night shift, using document analysis, interview, participant observation as data collection techniques, which corroborated the research objectives. The analysis of the collected data is based on three categories according to our theoretical framework, being Category 1 - Pedagogical knowledge, Category 2 - Content knowledge, Category 3 - Experience knowledge, with which we will discuss collected data. The results allowed us to draw an overview of how the formation of Teachers in High School occurs about Mathematics aimed at the Initial Years of Elementary School. We present, as an educational product, together with the research, a booklet to be disseminated in the Normal School researched.